Characterization And Potential Industrial Appication Of Gypsum Rich Waste - Zailan, Nur Nadhirah (Universiti Sains Malaysia, 2018)
NUF Gypsum rich waste which is by product from REE processing was characterized and analyzed to compare between natural gypsum and evaluate their quality suitability for specific industrial application. They were analysed by using X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Differential Scanning Calorimetric (DSC) / Thermogravimetric Analysis (TGA) and X-Ray Fluorescene (XRF) analysis. Other test included pH test, LOI, moisture, specific gravity and plasticity test are also done. The present characteristic bond of water vibration at 3606-3558cm-1 and sulfate vibration at 1151cm-1 in FTIR test indicates the present of gypsum anhydrate (CaSO4.2H2O). The SEM photomicrograph also shown the presence of hexagonal shape of gypsum and followed by composition of Calcium Oxide (CaO) and sulfite (SO3) obtained in XRF analysis which lead to formation of gypsum. The XRD results also indicate the presence of gypsum and calcite phase crystallinity. The gypsum rich waste is suitable to be used for agriculture and gypsum board industry since it met all the industrial specification. The high contain of Magnesium, Mg which is 5.87% is suitable for plant growth as it can act as soluble salt for the nutrient supply. It also suitable for gypsum board application since the content would not disturb the hydration process of gyspum board. The content of silica (SiO2) 0.62%, Chlorine (Cl) 2.8% and Na (Sodium) 0.7% meet the specification of agriculture and gypsum board industry. The iron content in the gypsum waste is quite high for the high grade of gypsum board application . One of the way to reduce the iron content is by using organic acid leaching method. Plasticity index value obtained is significantly optimum which is 19.78 which lead to a good strenght for gypsum board application.